Isle of Elsi : the dragon's librarian - Longstreth, Alec (Phase Seven Comics, 2019)
In The Dragon's Librarian, our pun-loving protagonist, Rex Jargon Jr. and his best friend Sally Sanders must save their village from a diabolical dragon. In A Menagerie of Messengers, Draziw the Wizard experiments with a bunch of new animal messengers, including talking wolves, after his beloved owl Nicomedes passes away. In The Search for Spinoza, Nogard the Dragon goes on a quest to find a pair of glasses with the right prescription to help him read books. (less).